Dietary cumulative acute risk assessment of organophosphorus, carbamates and pyrethroids insecticides for the Brazilian population. (February 2018) - Jardim, Andreia Nunes Oliveira; Brito, Alessandra Page; van Donkersgoed, Gerda; Boon, Polly E.; Caldas, Eloisa Dutra
Abstract: Cumulative acute dietary risk assessments of organophosphorus (OPs), carbamates (CBs) and pyrethroids (PYs) were conducted for the Brazilian population. Residue data for 30786 samples of 30 foods were obtained from two national monitoring programs and one University laboratory, and consumption data from a national survey conducted among persons 10 years or older. Acephate and methamidophos were used as index compounds (IC) for OPs, oxamyl for CBs and deltamethrin for PYs. Exposures were estimated using the Monte Carlo Risk Assessment (MCRA 8.2) software. Orange and orange juice (mainly containing methidathion), pasta and salted bread (mainly pirimiphos-methyl) contributed most to the OPs intake. Rice accounted for 80% of the CBs intake (teenagers), mainly due to aldicarb. Pasta, salted bread and beans contributed most to the PYs intake (9–14%), mainly due to bifenthrin. The intake did not exceed the ARfD at the 99.9th percentile for OPs, CBs and PYs, and the risks from the exposure were not considered of health concern. When food consumption data become available for children under age 10, studies in the cumulative exposure should be conducted, as this age group is the most critical among the population, mainly due to their higher food consumption per kg body weight. Highlights: Organophosphorus, carbamates, pyrethroids cumulative intakes not of health concern. Orange/juice, pasta, bread contributed most to OPs intake (methidathion/pirimiphos-M). Rice contributed most to CBs intake, mainly aldicarb. Pasta, salted bread, beans contributed most to PYs intake (bifenthrin).